Diseño de completamiento no convencional para su implementación en un pozo exploratorio en las formaciones porquero y depósitos gravitacionales (MTC) con diferentes gradientes de presión en el Valle Inferior del Magdalena (2020)
This project proposes the scenarios that can occur in an exploratory oil well located in the Lower Magdalena Valley where the aim is to test the mass transport complex and gravitational deposits; the last one has never been tested before in Colombia. Those scenarios are proposed through correlations based on seismic data, structural aspects, and geological arrangements of nearby wells. From the predetermined characteristics, three completion arrangements are made: one dual, one selective and one single, made up of tools not conventionally used that face the worst scenarios that can be found in the exploratory well. These three models are due to the need to provide different production options for the exploratory well. The financial viability of each completion arrangement is determined using the cost-benefit indicator to determine modifications that are suitable if its implementation is defined.